Observations on pollination, fecundity/siring ability and seed germination in Hevea brasiliensis - Chandrasekhar T R; Alice J; Gireesh T; Rao G P; Saraswathyamma C K (Journal of Rubber Research, 2004)
The major objective of this paper is to discuss the far higher hand-pollination success noted in some of the crosses of the hand pollination programme of the Rubber Research Institute of India conducted during 2002. As part of the ongoing activity, selected wild accessions (A) of Hevea brasiliensis were crossed with cultivated clones (W) for widening the genetic base of the breeding population. Hand pollinations were carried out following the conventional method for eight days between 9.30 a.m and 1.30 p.m on each day. Pollination success in W x A crosses ranged from nil to 14.2;while in W x W crosses it was 0.8;to 19;. Among the female parents, clone PB 330 gave an average success rate of 16.7;with more than 50;success in many of the groups of pollinations. Wild accession MT 2226 produced the best pollination success as male parent (12.1;). Between first fruit count and their maturity nearly 100;fruit retention was observed indicating negligible fruit loss in later stages of fruit development. Seed germination percentage in WA crosses ranged from 37.5;to 83.3;with an average of 65;while in the WW crosses it was 50;to 100;with a mean of 82.6;. Seeds sired by MT 2226 germinated within a few days of putting them for germination appeared to posses an inherent capacity for forcing early germination of seeds. The pollination results indicated that cultivated clone PB 330 as having high fecundity and germplasm accession MT 2226 as high siring ability parents.
Keywords: Fecundity; Hevea brasiliensis; Pollination; Seed germination; Siring ability; Wickham clones; Wild germplasm